2020
DOI: 10.21203/rs.3.rs-116263/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Second-harmonic generation and the conservation of spatiotemporal orbital angular momentum of light

Abstract: Light with spatiotemporal orbital angular momentum (ST-OAM) is a recently discovered type of structured electromagnetic field with characteristic space-time spiral phase structure and transverse OAM. In this work, we present the first generation and characterization of the second-harmonic of ST-OAM pulses. By uncovering the conservation of transverse OAM in a second-harmonic generation process, where the space-time topological charge of the fundamental field is doubled along with the optical frequency, we esta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…It can be clearly seen that the ST vortex with = 1 is converted into the second-harmonic vortex with = 2 during the nonlinear frequency doubling. This process could be expressed as 28…”
Section: ■ Nonlinear Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be clearly seen that the ST vortex with = 1 is converted into the second-harmonic vortex with = 2 during the nonlinear frequency doubling. This process could be expressed as 28…”
Section: ■ Nonlinear Interactionmentioning
confidence: 99%
“…A scaling rule similar to the longitudinal OAM was uncovered, in which the Nth harmonic has a topological charge of N . As shown in Figure 5a, by cascading a nonlinear barium borate crystal (BBO) at the output of the ST vortex generator, Guan Gui et al 28 studied the nonlinear second-harmonic generation process of the transverse OAM beams. Hancock et al 29 demonstrated similar experimental results almost simultaneously (Figure 5b).…”
Section: ■ Nonlinear Interactionmentioning
confidence: 99%